Acute Lymphoblastic Leukemia: Fourteen Years Experience of a Single Institution - Sah, KP; Shrestha, PN (Journal of Nepal Paediatric Society, 2014)
Introduction: Leukemia commonly known as blood cancer is the most common malignant neoplasm in childhood accounting for about 41 % of all malignancies that occur in children younger than 15 year of age. The objectives of this study were to find out the clinico-laboratory features and survival of children with acute lymphoblastic leukemia (ALL) during fourteen years in pediatric oncology unit of a tertiary care hospital. Materials and Methods: This was a retrospective study conducted at Kanti Children’s Hospital (KCH) from March 1998 to March 2012. Bone marrow aspiration showing ≥25 % blast cells was the criteria for diagnosis of ALL. Results: Out of 755 childhood cancers reported in this hospital during study period, total number of Acute leukemia patients were 375 (49.7%). Among acute leukemia, patients with ALL were 300, which was 80.0 % among all leukemias and 39.7% of all cases of cancers. Among cases of ALL, L1, L2 and L3 constituted 163 (54.3%), 131 (43.7%) and 6 (2%) respectively. The age of the children with acute leukemia ranged from six months to fourteen years, with a mean age of 7.3 years. The majority of children (61.7 %) with ALL fell into the age group of 2-9 years. Males: Female ratio was (M:F=1.3:1 ). The most common presenting features in ALL were fever (89.2 %), followed by splenomegaly (89.1%), hepatomegaly (69.2%) and lymphadenopathy (58.4 %). Among all patients, remission rate was 28.3% at ≥ 5 years, 17.7% were on maintenance, 30.3% abandoned treatment and 23.7 % died. Conclusion: This study showed that the patients on remission at ≥ 5 years in this centre were 28.3%. DOI: http://dx.doi.org/10.3126/jnps.v34i1.9056 J Nepal Paediatr Soc 2014;34(1):1-6